KNOWLEDGE AND ATTITUDE OF MIDWIVES REGARDING THE ENHANCEMENT OF BREAST MILK PRODUCTION (ASI) THROUGH LACTATION MASSAGE - Nisa, Juhrotun; Hidayah, Seventina Nurul; Chikmah, Adevia Maulidya; Harnawati, Riska Arsita (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Inadequate breast milk production for newborns might result in impaired growth and development. Enhancing breast milk production can be achieved by lactation massage, a therapeutic technique including massage movements on the breast area that stimulates lymphatic and blood circulation, increases milk production, and alleviates issues related to blocked milk ducts. The applicability of this scientific findings to health services is limited; therefore, midwifery support is essential in enhancing breast milk production with lactation massage. Midwives can utilize their expertise to perform lactation massage, thereby enhancing breast milk supply and promoting the effectiveness of exclusive breastfeeding. This study aimed to ascertain the correlation between midwives' knowledge and attitudes on the enhancement of breast milk production by lactation massage. The method used was cross-sectional, and the target population consists of midwives attending Harapan Bersama Polytechnic. Utilizing a total sampling technique involving 11 individuals. Data were acquired by surveys and subsequently analyzed using the chi-square method. The study's results yielded a P value of 0.04 (α0.05), indicating a correlation between midwives' knowledge and attitudes on the enhancement of breast milk supply via lactation massage, with an odds ratio of 0.33. Midwives' knowledge and abilities must be improved in order to use lactation massage to boost the supply of breast milk.